2020
DOI: 10.20417/nzjecol.44.8
|View full text |Cite
|
Sign up to set email alerts
|

Movement behaviour of a translocated female ship rat and her offspring in a low rat density New Zealand forest

Abstract: Dispersal is a fundamentally important aspect of animal behaviour, but empirical data describing it are lacking for many species. Here, we report on a field study aimed at measuring post-weaning movement distances of juvenile ship rats (Rattus rattus) and their mother away from a known natal nest site in an area with low conspecific population density. The movement behaviour of invasive species at low density is of particular interest, as it can inform design of surveillance arrays to detect incursion into pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We know of only one published study that has tested how resident ship rat movements change following large‐scale control operations that result in the loss of most of their neighbors, which found that movement (as measured by SECR) did not significantly change (O'Malley et al, 2022). However, it is possible that over time, these survivor rats may move large distances as they search for conspecifics, as has been found for rats placed in novel environments with low rat densities (e.g., Nathan et al, 2020; Russell et al, 2010). In addition, one‐off control early in the irruption may mean that low‐ and mid‐elevation rats that survive the operation have enough time and resources available for the population to regrow rapidly and reach high densities by the spring, when nesting birds are vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know of only one published study that has tested how resident ship rat movements change following large‐scale control operations that result in the loss of most of their neighbors, which found that movement (as measured by SECR) did not significantly change (O'Malley et al, 2022). However, it is possible that over time, these survivor rats may move large distances as they search for conspecifics, as has been found for rats placed in novel environments with low rat densities (e.g., Nathan et al, 2020; Russell et al, 2010). In addition, one‐off control early in the irruption may mean that low‐ and mid‐elevation rats that survive the operation have enough time and resources available for the population to regrow rapidly and reach high densities by the spring, when nesting birds are vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the spatial scale of detection derived from our SECR modeling suggested that home ranges of rats on middle elevation grids were reasonably small (radius of 47.8 m in July 2019, assuming a circular home range; Carpenter, unpublished data), as would be expected from a high-density population. In a south Westland beech forest with very low rat density, natal dispersal ranged from 128 to 675 m (Nathan et al, 2020), which implies that dispersing juvenile rats would be capable of moving the 550-650 m between our mid-and high grids. However, we hypothesize that the process was less one of long-distance dispersal of rats upslope and more one of rat individuals increasingly settling uphill as they occupied available habitat.…”
Section: F I G U R Ementioning
confidence: 96%
“…Sample size might limit these analyses but results suggest that these four rat populations experience as much gene flow as the Picton forest samples despite their greater geographic distances (> 100 km). Although the distance that individual ship rats can move is understood to be between several hundred metres and 1.5 km (Innes et al 2011 ; Nathan et al 2020 ), the population samples of ship rat in the North Island most likely represents a continuous distribution of this species through the Tararua Ranges and adjacent landscape (Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although natal dispersal in rodents generally (Krebs et al 2007) and in Norway rats (R. norvegicus) has been regarded as male-biased (Calhoun 1962), subsequent studies have found that some females also move large distances (Heiberg et al 2012). Nathan et al (2020) recorded natal dispersal distances in ship rats, but the sample size was too small to determine differences in males (n = 2) versus females (n = 1). We know of no other natal dispersal studies of ship rats, but we found that among the adult ship rats we studied, females were just as likely to make large movements into the operational area as males.…”
Section: Discussionmentioning
confidence: 99%
“…Although ship rat home range lengths are typically in the range of 100-300 m (Innes & Russell 2021), rats may make far greater movements in large areas with very few rats. For example, Nathan et al (2020) found that a biomarked ship rat mother moved over 1500 m, and her offspring moved up to 675 m, from the release site in a post-1080 zone to which they had been translocated. Radio-collared adult male ship rats experimentally placed in Maungatautari sanctuary also made large movements of up to 1100 m, perhaps to search for mates (Innes et al 2011).…”
Section: Discussionmentioning
confidence: 99%